2017
DOI: 10.1186/s13071-017-2001-3
|View full text |Cite
|
Sign up to set email alerts
|

Parasite responses to pollution: what we know and where we go in ‘Environmental Parasitology’

Abstract: Environmental parasitology deals with the interactions between parasites and pollutants in the environment. Their sensitivity to pollutants and environmental disturbances makes many parasite taxa useful indicators of environmental health and anthropogenic impact. Over the last 20 years, three main research directions have been shown to be highly promising and relevant, namely parasites as accumulation indicators for selected pollutants, parasites as effect indicators, and the role of parasites interacting with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
212
2
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 264 publications
(261 citation statements)
references
References 196 publications
7
212
2
6
Order By: Relevance
“…Interestingly, the palladium concentration in the tissues of infected hosts (after removal of the parasite) was 2 times higher than the concentration in the uninfected amphipods (Sures & Radszuweit 2007). These results are somewhat contradictory to studies on metal accumulation patterns in adult acanthocephalans, which usually have higher levels of metals than their hosts (Sures & Siddall 2003, Nachev & Sures 2016, Sures et al 2017b). Moreover, the very high metal accumulation in adult acanthocephalans may lead to reduced metal concentrations in host tissues (Sures & Siddall 1999, Filipović Marijić et al 2014).…”
Section: Acanthocephalamentioning
confidence: 68%
See 4 more Smart Citations
“…Interestingly, the palladium concentration in the tissues of infected hosts (after removal of the parasite) was 2 times higher than the concentration in the uninfected amphipods (Sures & Radszuweit 2007). These results are somewhat contradictory to studies on metal accumulation patterns in adult acanthocephalans, which usually have higher levels of metals than their hosts (Sures & Siddall 2003, Nachev & Sures 2016, Sures et al 2017b). Moreover, the very high metal accumulation in adult acanthocephalans may lead to reduced metal concentrations in host tissues (Sures & Siddall 1999, Filipović Marijić et al 2014).…”
Section: Acanthocephalamentioning
confidence: 68%
“…According to the present knowledge, it is obvious that the impact of parasites can confound the outcome of toxicological and ecotoxicological studies in various ways. Therefore, parasites in amphipods and other test organisms should be considered in ecotoxicological studies, as already suggested by several authors (Ford & Fernandes 2005, Sures 2008a, Ford 2012, Sures et al 2017b. In this context, it would also be an important aim to relate the effect size of parasite impacts to the effects of other influencing factors, to obtain a quantitative estimate of the relevance of parasites on the outcome of ecotoxicological studies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations